Sustainable Food Systems in India: A Pathway to Overcoming Food Insecurity (Advances in Applied Biological Research, 2025)
With a population of 1.43 billion, India surpassed China in 2023 to become the  most populous country, accounting for nearly 18% of the world’s total population.  This surge has raised major concerns, including increased pressure on natural re sources, rising unemployment, strain on healthcare and education systems, urban  overcrowding and environmental degradation. One of the most pressing challeng es is ensuring sustainable food systems that can meet the nutritional needs of this  vast population without compromising the environment. Despite major advance ments in India’s agricultural sector and a rise in food crop production, the nation  continues to face challenges in ensuring a sufficient food supply for its entire pop ulation. Many Indians continue to experience food insecurity and hunger, contrib uting to the double burden of malnutrition, marked by a high prevalence of under nutrition alongside a growing incidence of obesity, largely driven by poor dietary  quality. Given these challenges, transitioning to a sustainable food system is not  just desirable but essential for India. A sustainable food system has the potential  to simultaneously improve nutrition, protect the environment, support livelihoods  and ensure equitable access to food. However, achieving this requires addressing  systemic obstacles while leveraging the opportunities offered by innovation, tradi tional knowledge and policy reform. This review aims to explore the current status  of India’s food system, examine the opportunities for promoting sustainability and  identify key barriers that hinder progress.
Keywords: India; food systems; food security; sustainable food system; environmental sustainability